Inhibitory effect of a Brazilian marine brown alga Spatoglossum schröederi on biological activities of Lachesis muta snake venom - Domingos,Thaisa Francielle Souza (2012)
The ability of crude extracts of the brown seaweed Spatoglossum schröederi to counteract some of the biological activities of Lachesis muta snake venom was evaluated. In vitro assays showed that only the extract of S. schröederi prepared in ethyl acetate was able to inhibit the clotting of fibrinogen induced by L. muta venom. On the other hand, all extracts were able to inhibit partially the hemolysis caused by venom and those prepared in dichloromethane or ethyl acetate fully neutralized the proteolysis and hemorrhage produced by the venom. Moreover, the dichloromethane or ethyl acetate extracts inhibited the hemolysis induced by an isolated phospholipase A2 from L. muta venom, called LM-PLA2-I. In contrast, the hexane extract failed to protect mice from hemorrhage or to inhibit proteolysis and clotting. These results show that the polarity of the solvent used to prepare the extracts of S. schröederi algae influenced the potency of the inhibitory effect of the biological activities induced by L. muta venom. Thus, the seaweed S. schröederi may be a promising source of natural inhibitors of the enzymes involved in biological activities of L. muta venom.